PELATIHAN STRATEGI MENINGKATKAN KOSAKATA BAHASA INGGRIS MENGGUNAKAN CROSSWORD PUZZLE PADA SISWA SDN 20 NAN SABARIS PARIAMAN - Annisha Dyuli Adha; Andriani, Desi; Dania, Rahma (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
English is one of the subjects that the students learn in the school. Although it has been studied since elementary school, English is still one of the subjects that are considered difficult and boring by the students, because English is not their mother tongue. Therefore, teachers in the schools must be creative in teaching English so that the students become interested in learning it. Especially for elementary students, the teachers can teach English by using playing tricks while learning so that it can trigger the students' enthusiasm to learn, so that learning English becomes something fun. One strategy that can be implemented is learning while playing by using Crossword Puzzles. This can add or improve the students' vocabulary in learning English. For this reason, this activity aims to train the students to learn English to be fun by using Crossword Puzzles. The output target of this activity is to help the students in growing their interest in learning English and to help them to improve their English vocabularies in a fun way.